Prevalence and perceived outcomes of complementary and alternative medicine use in hospitalized British patients - Win Winit-Watjana; Nusirat Bello; Wasim Baqir; Alan Worsley (Archives of Global Professionals, 2012)
Objectives: This study aimed to investigate the prevalence and perceived outcomes of complementary and alternative medicine (CAM) use in secondary care patients and to find out determinants for CAM utilization and perceived effectiveness and side-effects. Materials and Methods: Patients who met the eligibility criteria in this cross-sectional study were interviewed using a semi-structured questionnaire. Patients' medications and relevant details were verified from the medical notes. A logistic regression analysis was performed and the significance level set at α = 0.05. Results: A total of 240 in-patients were interviewed. The prevalence of CAM use during admission, within 1 month, within 1 year, and at some point in life was 90.4%, 68.8%, 37.9%, and 8.3%, respectively. Diverse reasons for CAM use or non-use were cited. Nearly two-thirds of patients (63.1%) perceived CAM effectiveness and approximately half (57.6%) were aware of its side-effects. The determinants for CAM use at some point in life and perceived effectiveness could be predicted approximately 20% by two models: Logit P use = 3.404 − 1.044 × Educ + 1.314 × Ward − 1.539 × Consider and Logit P eff = 3.244-0.995 × Gender-0.025 × Age − 1.503 × Consider. Conclusion: Patients decided to use CAM for various reasons and perceived different outcomes. The specific CAM use and its outcomes warrant further studies.